Cover Image. (May 2017) - Sun, Xiaoyu; Mao, Yixin; Dai, Panpan; Li, Xumin; Gu, Weiyan; Wang, Huining; Wu, Gang; Ma, Jianfeng; Huang, Shengbin
Abstract : The cover image, by Xiaoyu Sun et al ., is based on the Animal Experiment Mitochondrial dysfunction is involved in the aggravation of periodontitis by diabetes, DOI:10.1111/jcpe.12711 .